A systematic review showed more consideration is needed when conducting nonrandomized studies of interventions - Dhiman, Paula; Lee, Hopin; Kirtley, Shona; Collins, Gary S. (Journal of clinical epidemiology, 2020)
The objective of this study was to evaluate the methodological conduct, reporting, and risk of bias of nonrandomized studies of interventions (NRSIs) funded by UK National Institute for Health Research Biomedical Research Centres (NIHR-BRCs). We conducted a systematic review, searching the Medline and Web of Science databases between 2012 and 2018, for NRSIs funded by NIHR-BRCs. Eligible studies were published between April 2012 and December 2017. We selected a contemporary subset of NRSIs published in 2017. We extracted study design, methods for overcoming confounding bias from nonrandomization, analysis methods, and items for assessing risk of bias. Risk of bias was the primary outcome, assessed using Risk Of Bias In Non-randomised Studies–of Interventions (ROBINS-I). Fifty-two NSRI publications were included, of which over half were cohort studies and 29% before-and-after studies. Seventy-seven percent analyzed nonpurposefully collected data. All had serious or critical risk of bias. Regression adjustment was most commonly used to address confounding bias (50%). Few (12%) studies accounted for missing data and 42% reported different numbers of outcomes in their methods and results. Most reviewed NRSIs had serious or critical risk of bias. Although NRSIs can evaluate treatment effects when appropriately conducted, this review shows that their design, analysis, and reporting require more consideration.